2009
DOI: 10.1016/j.actamat.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solute and vacancy segregation on migration of a/4〈1 1 1〉 and a/2〈1 0 0〉 antiphase boundaries in Fe3Al

Abstract: Effects of segregation of solute atoms and vacancies on migration of a/4<111> and a/2<100>antiphase domain boundaries (APDBs) in stoichiometric Fe 3 Al at various temperatures are studied using a phase-field model [Koizumi et al., Acta Mater. 2008;56:5861]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…Since the details of the phase-field model we developed are available in the previous papers [16,17], only the characteristics of our model are briefly described here. The model we developed is based on the Bragg-Williams model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the details of the phase-field model we developed are available in the previous papers [16,17], only the characteristics of our model are briefly described here. The model we developed is based on the Bragg-Williams model.…”
Section: Methodsmentioning
confidence: 99%
“…This deviation may be due to some segregation. For shedding light on the effects of vacancy segregation, we developed a phase-field model in which local vacancy concentration was taken into account [16,17]. In the latest study [17], we performed simulations of APB migration in the stoichiometric Fe 3 Al, and found that the migration of B2-APB and D0 3 -APB were affected by solute and vacancy segregation in different manners [17].…”
Section: Introductionmentioning
confidence: 99%
“…Here, only the characteristics of our model are briefly described since the details of the phase-field model we developed are available in the previous papers [16,17]. The model is based on the Bragg-Williams model.…”
Section: Methodsmentioning
confidence: 99%
“…This deviation may arise from some segregation. To shed light on the effects of vacancy segregation, we developed a phase-field model in which local vacancy concentration was taken into account [16,17]. We found that the migration of B2-APB and D0 3 -APB in Fe 3 Al were affected by solute and vacancy segregation in different manners [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation